Faktor Risiko yang Mempengaruhi Kematian Maternal - Cruz, Jermias da (Journal of Telenursing (JOTING), 2024)
This study aims to determine the risk factors that influence maternal mortality, which consist of close determinants, intermediate determinants, and distant determinants. The method used is observational with a case-control study. The research results obtained show that the risk factors that influence maternal mortality based on multivariate analysis are pregnancy complications and late referral. In conclusion, maternal deaths are influenced by various factors such as delays in referral, especially the first delay, low levels of maternal education, low levels of family income, and the inability to implement the Mother Love Movement (GSI) optimally throughout Ermera Municipality as the government's effort to reduce maternal deaths. Keywords: Risk Factors, Maternal Death, Case-Control Study